Mental health and labor supply: Evidence from Canada - Yichen Shen (Elsevier, 2023)
This study investigates the relationship between mental health and employment using an instrumental variable approach with the 2012 Canadian Community Health Survey-Mental Health. Using a family member's mental health problem(s) as an instrument for poor mental health, the estimates reveal that poor mental health significantly reduces employment outcomes. These findings are robust to various specifications, such as an alternative instrument and a relaxation of the exclusion restriction assumption. In addition, the relationship is driven mainly by men and younger workers. Moreover, the findings suggest that the relationship is mediated by a decline in cognitive abilities, such as difficulties in concentration and motivation, and social relations with acquaintances and friends. Finally, the estimates show that this phenomenon is contagious: poor mental health has a significant spillover effect on coworkers' mental health in workplaces. This study demonstrates the importance of mental health illness in Canada and other developed countries.